Selective Role of the Putamen in Serial Reversal Learning in the Marmoset - Jackson, Stacey A W; Horst, Nicole K; Axelsson, Sebastian F A; Horiguchi, Naotaka; Cockcroft, Gemma J; Robbins, Trevor W; Roberts, Angela C (Cerebral cortex (New York, N.Y. 1991), 2019)
Abstract Fronto-striatal circuitry involving the orbitofrontal cortex has been identified as mediating successful reversal of stimulus-outcome contingencies. The region of the striatum that most contributes to reversal learning remains unclear, with studies in primates implicating both caudate nucleus and putamen. We trained four marmosets on a touchscreen-based serial reversal task and implanted each with cannulae targeting both putamen and caudate bilaterally. This allowed reversible inactivation of the two areas within the same monkeys, but across separate sessions, to directly investigate their respective contributions to reversal performance. Behavioral sensitivity to the GABAA agonist muscimol varied across subjects and between brain regions, so each marmoset received a range of doses. Intermediate doses of intra-putamen muscimol selectively impaired reversal performance, leaving the baseline discrimination phase unchanged. There was no effect of low doses and high doses were generally disruptive. By contrast, low doses of intra-caudate muscimol improved reversal performance, while high doses impaired both reversal and baseline discrimination performance. These data provide evidence for a specific role of the putamen in serial reversal learning, which may reflect the more habitual nature of repeated reversals using the same stimulus pair.